2021
DOI: 10.1080/14015439.2021.1873415
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in vocal doses among occupational voice users: a systematic review of literature and meta-analysis

Abstract: Background: Occupational voice users such as teachers, singers, and broadcasters have high vocal demands increasing the risk for developing voice disorders. Among occupational voice users, the literature has report gender differences in vocal doses as part of vocal demands. However, these differences have not been quantified. Objective: To determine differences per gender on vocal doses among different groups of occupational voice users. Methods: A systematic review of literature and meta-analysis were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Gender influences faith leaders’ vocal health experiences, with female faith leaders more likely to report experiencing voice symptoms and problems (Hagelberg & Simberg, 2015 ). This mirrors broader research assertions that females experience higher vocal loads associated with differences in laryngeal structures, body functioning, psychosocial factors, life-domain functioning and that females more readily engage in help-seeking (Atará-Piraquive & Cantor-Cutiva, 2021 ; dos Santos et al, 2019 ; Hunter et al, 2011 ; Lyberg-Åhlander et al, 2019 ).…”
Section: Scoping Review Findingssupporting
confidence: 68%
“…Gender influences faith leaders’ vocal health experiences, with female faith leaders more likely to report experiencing voice symptoms and problems (Hagelberg & Simberg, 2015 ). This mirrors broader research assertions that females experience higher vocal loads associated with differences in laryngeal structures, body functioning, psychosocial factors, life-domain functioning and that females more readily engage in help-seeking (Atará-Piraquive & Cantor-Cutiva, 2021 ; dos Santos et al, 2019 ; Hunter et al, 2011 ; Lyberg-Åhlander et al, 2019 ).…”
Section: Scoping Review Findingssupporting
confidence: 68%
“…The participants were asked to read a text aloud in a quiet and a noisy condition. The voice was recorded using a voice dosimeter, which can provide an authentic picture of vocal demand responses [ 59 ]. In contrast to laboratory situations, this study was performed in a semi-controlled real situation with a live audience and voice changes were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several vocal dose metrics such as distance dose (Dd), cycle dose, and time dose were successfully derived from NSA signals by our group and others [11,[24][25][26][27]. However, inconclusive literature suggested that these metrics could be gender dependent, which may implicate the need for creating gender-specific vocal safety limits [28]. An investigation on the quantitative relationship between vocal doses and NSA-derived acoustic metrics in both females and males is thus pivotal to validate this critical question.…”
Section: Introductionmentioning
confidence: 99%